ANALISIS KORELASI KONDISI SOSIAL EKONOMI ORANGTUA DAN EFIKASI DIRI TERHADAP PRESTASI BELAJAR IPS - Saprudin Saprudin; Wahjoedi Wahjoedi; Utami Widiati (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2017)
This research is aimed to know (1) The correlation between social and economic conditions of students’ parents with their achievement in learning Social Study (2) the correlation between self effication with achievement in learning social study (3) The correlation of both social and economic conditions of students’ parents and self effication with their achievement in learning Social Study in Grade VIII of SMPN 1 Salopa. The whole population on this research is 216 students, so 68 students are taken as a sample in the way of random sampling. The method of this research is correlation analysis, data is obtained from the questioner answered by respondents and documentation from 68 students. The result of this research showed that (1) social and economic conditions of students’ parents has a significant and positive correlation with their achievement in learning Social Study with coeficent correlation 0,648 and significancy 0,000 (2) self effication has a significant and positive correlation with achievement in learning social study with coeficent correlation 0,610 and significancy 0,000 (3) both social and economic conditions of students’ parents and self effication has a significant and positive correlation with their achievement in learning Social Study with coeficent correlation 0,719 and significancy 0,000.Tujuan penelitian ini untuk mengetahui adanya (1) hubungan antara kondisi sosial ekonomi orangtua dengan prestasi belajar IPS, (2) hubungan antara efikasi diri dengan prestasi belajar IPS, (3) hubungan secara bersama-sama kondisi sosial ekonomi, efikasi dengan prestasi belajar IPS di kelas VIII SMP Negeri 1 Salopa. Populasi dalam penelitian ini siswa kelas VIII sebesar 216 siswa sehingga diambil sampel secara sample random sampling sebesar 68 siswa.  Metode penelitian ini analisis korelasi, data diperoleh dari angket yang dijawab responden dan dokumentasi dari 68 siswa. Hasil penelitian menunjukkan bahwa (1) kondisi sosial ekonomi orangtua memiliki hubungan yang signifikan dan positif  dengan prestasi belajar IPS dengan nilai koefisien korelasi 0,648 dengan signifikan 0,000,  (2) efikasi diri memiliki hubungan yang signifikan dan positif dengan prestasi belajar IPS dengan koefisien korelasi 0,610 dengan signifikasi 0,000, (3) kondisi sosial ekonomi orangtua, efikasi diri memiliki hubungan yang signifikan secara bersama dengan prestasi belajar untuk kofisien korelasi 0,719 dan sigifikansi 0,000.